Ginseng-derived nanoparticles alter macrophage polarization to inhibit melanoma growth. Issue 1 (27th November 2019) - Cao, Meng; Yan, Huaijiang; Han, Xuan; Weng, Ling; Wei, Qin; Sun, Xiaoyan; Lu, Wuguang; Wei, Qingyun; Ye, Juan; Cai, Xueting; Hu, Chunping; Yin, Xiaoyang; et al.
Abstract : Background: It is unclear whether plant-derived extracellular vesicles (EVs) can mediate interspecies communication with mammalian cells. Tumor-associated macrophages (TAMs) display a continuum of different polarization states between tumoricidal M1 phenotype and tumor-supportive M2 phenotypes, with a lower M1/M2 ratio correlating with tumor growth, angiogenesis and invasion. We investigated whether EVs from ginseng can alter M2-like polarization both in vitro and in vivo to promote cancer immunotherapy. Methods: A novel EVs-liked ginseng-derived nanoparticles (GDNPs) were isolated and characterized from Panax ginseng C. A. Mey. Using GDNPs as an immunopotentiator for altering M2 polarized macrophages, we analyzed associated surface markers, genes and cytokines of macrophages treated with GDNPs. Mice bearing B16F10 melanoma were treated with GDNPs therapy. Tumor growth were assessed, and TAM populations were evaluated by FACS and IF. Results: GDNPs significantly promoted the polarization of M2 to M1 phenotype and produce total reactive oxygen species, resulting in increasing apoptosis of mouse melanoma cells. GDNP-induced M1 polarization was found to depend upon Toll-like receptor (TLR)-4 and myeloid differentiation antigen 88 (MyD88)-mediated signaling. Moreover, ceramide lipids and proteins of GDNPs may play an important role in macrophage polarization via TLR4 activation. We found that GDNPs treatment significantly suppressed melanoma growth in tumor-bearing mice with increased presence of M1 macrophages detected in the tumor tissue. Conclusions: GDNPs can alter M2 polarization both in vitro and in vivo, which contributes to an antitumor response. The polarization of macrophages induced by GDNPs is largely dependent on TLR4 and MyD88 signalling. GDNPs as an immunomodulator participate in mammalian immune response and may represent a new class of nano-drugs in cancer immunotherapy.